Search for the chiral magnetic effect in Au+Au collisions at √sNN=27 GeV with the STAR forward event plane detectors - Aboona, Bassam; Deppner, Ingo Martin; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physics letters, 2023)
A decisive experimental test of the Chiral Magnetic Effect (CME) is considered one of the major scientific goals at the Relativistic Heavy-Ion Collider (RHIC) towards understanding the nontrivial topological fluctuations of the Quantum Chromodynamics vacuum. In heavy-ion collisions, the CME is expected to result in a charge separation phenomenon across the reaction plane, whose strength could be strongly energy dependent. The previous CME searches have been focused on top RHIC energy collisions. In this Letter, we present a low energy search for the CME in Au+Au collisions at sNN=27 GeV. ...
Online veröffentlicht am 1. März 2023
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, NN ist dabei tiefgestellt
STAR Collaboration: B.E. Aboona, I.M. Deppner, Y.H. Leung, Y. Söhngen, P.C. Weidenkaff [und 362 weitere Personen]
Gesehen am 05.12.2023